Salidroside ameliorates memory impairment following long-term ethanol intake in rats by modulating the altered intestinal microbiota content and hippocampal gene expression - Jiao, Yu; Zhao, Zhenglin; Li, Xin; Li, Lulu; Xiao, Dan; Wan, Siyuan; Wu, Tong; Li, Tong; Li, Ping; Zhao, Rongjie (Frontiers in Microbiology, 2023)
Background Salidroside (Sal), the main component of a famous herb Rhodiola rosea L, enhances memory performance and reduces fatigue. Therefore, this study assessed the effect of Sal on memory impairment induced by a long-term intake of ethanol (EtOH) in rats and investigated its relevant mechanisms using gut microbiota metagenomic analysis and hippocampal transcriptomic analysis. Methods Eighteen male SD rats were divided into the normal control group (CON group), EtOH model group (Model group), and Sal treatment group (Sal group). The rats in the Model and Sal groups intragastrically (i.g.) received 2 g/kg EtOH for 30 consecutive days, whereas the CON group was given an equal volume of distilled water. Meanwhile, the rats in the Sal group were administered i.g. 30 mg/kg Sal 60 min after EtOH intake. All rats were tested in the eight-arm maze for their memory function every 3 days. On the 30th day, metagenomic analyses of gut microbiota and transcriptomic analyses of the hippocampus were performed. Results Compared with the Model group, Sal treatment reduced the total time to complete the eight-arm maze task, decreased the number of arm entries, and abated the working memory error that was significant from the 9th day. Additionally, Sal intervention improved the gut microbiota composition, such as the increased abundance of Actinobacteria and Bifidobacterium, which was related to the metabolism of amino acids and terpenoid carbohydrate, endocrine function, and signal transduction by neurotransmitters. In the hippocampus, the EtOH intake differentially expressed 68 genes (54 genes increased, whereas 14 genes decreased), compared with the CON group, whereas Sal intervention affected these changes: 15 genes increased whereas 11 genes decreased. And, enrichment analyses revealed these genes were related to the structural components of the ribosome, mRNA splicing process, protein translation, mitochondria function, and immunological reaction. Finally, a correlation analysis found the memory impairment was positively correlated with the abnormal upregulation of Tomm7 but negatively correlated with decreased abundance of gut Alistipes_indistinctus, Lactobacillus_taiwanensis, Lactobacillus_paragasseri, and Lactobacillus johnsonii. Conclusion Sal improved memory impairment caused by long-term EtOH intake in rats, which may be related to its regulation of gut dysbiosis and hippocampal dysfunction.